Learning-Outcomes Factors of Circular Business Model-Training for Waste-Bank Managers - Aprihatiningrum Hidayati; Andianto Widjaja; Ronny Kountur; Joni Phangestu (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Waste banks and reduce-reuse-recycle (3R) waste management sites are critical to addressing growing waste problems, but many face challenges in developing effective business models. Training in circular business models is crucial to empower waste bank managers for sustainable and profitable operations.Purpose: This study aims to assess the learning outcomes of circular business model training for waste banks and 3R waste management sites, focusing on competencies that can enhance waste management practices.Design/Methodology/Approach: A two-stage research design was employed. The first stage involved qualitative in-depth interviews with 19 participants, analyzed using content analysis. The second stage applied findings from the qualitative phase to design data collection instruments for a quantitative study, which included a survey of 39 managers. The quantitative data were analyzed through Exploratory Factor Analysis (EFA) using SPSS v26.Findings/Results: Seven critical learning outcomes were identified: planning, leadership, finance, self-efficacy, entrepreneurship, information sharing, and marketing. These factors represent essential competencies for the successful implementation of circular business models. Notably, self-efficacy emerged as a novel factor, emphasizing the psychological readiness of participants.Conclusion: The identified factors are key for successful circular business model adoption in waste management. Incorporating them into training programs can enhance waste bank and 3R site operations, leading to greater sustainability and profitability.Originality/Value: This research contributes new insights into the competencies required for circular business model training in waste management, particularly the role of self-efficacy in fostering successful outcomes. Keywords: circular business model, exploratory factor analysis, learning outcomes, training, waste banks